Medicinal use of cannabis-based products: a practical guide for paediatricians. Issue 2 (February 2020) - Ali, Sajeed; Parker, Alasdair PJ.
Abstract: In the context of intense media and societal scrutiny, on a background of limited scientific evidence, the prescription of cannabis based products for medicinal use (CBPMs) has led to much stress - for clinicians and parents alike- in the medical management of children and young people. This review aims to summarize the recent legal changes to CBPMs and highlights the current evidence for the use of these products in drug-resistant epilepsy and spasticity. The review offers practical guidance for clinicians seeing families who are seeking CBPMs, and summarizes recommended indications, risks and benefits of this group of medications in the management of children with neurodisabilities.